ANALISIS PROFITABILITAS PADA PT JASA RAHARJA PERWAKILAN BATURAJA - Aprilia, Irdina; Bramana, Sally Maria (Journal Economics Technology And Entrepreneur, 2025)
This study is entitled "Profitability Analysis at PT Jasa Raharja Representative Office in Baturaja." Based on the results of the profitability analysis at PT Jasa Raharja Representative Office in Baturaja, the profit margin in 2019 was 38.67%, in 2020 it was 56.43%. From the calculation data for 2019-2020, it can be seen that the profit margin has increased. In 2021, the profit margin calculation was 38.24%, and in 2022 it was 47.89%, while in 2023 it was 25.40%. From the calculation data for 2021-2023, it can be seen that the profit margin has increased and decreased. The calculation of Return on Assets (ROA) of PT Jasa Raharja Representative Office in Baturaja in 2019 was 23.96%, in 2020 it was 41.55%. From 2019-2020, the ROA data calculation has increased. In 2021, the ROA calculation was 23.44%, in 2022 the ROA calculation increased by 30.13%, while in 2023 it decreased by 20.33%. The Return on Equity (ROE) calculation in 2019 was 31.24%, in 2020 it was 53.98%. From the 2019-2020 calculation, the ROE calculation increased, in 2021 it was 29.98%, in 2022 the ROE calculation was 42.37%, while in 2023 the ROE data calculation was 26.09%. Based on data over the past five years, the ROE calculation has experienced increases and decreases.